EDUKASI BAHAYA MEROKOK PADA TINGKAT PENGETAHUAN MASYARAKAT DI DUSUN LEWOMUDAT DESA WAIPAAR - Yoseph Darius Purnama Rangga; Gardianus Irwanto Rapa; Yohana P. A. A. L; Gelo Lodo; Theresia Helfriati; Elisabeth Gare Ngole; Maria Konsita Ani Misa; Menge, Maria Helmiana Wea; Rosalia Kasilda (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
Smoking behavior is an activity or smoking activity that starts from burning, smoking until exhaling it out to cause cigarette smoke which is measured through perceptions and activities towards smoking. Cigarette smoke contains three of the most dangerous chemicals, namely tar, nicotine, and carbon monoxide. This activity aims to increase knowledge of the dangers of smoking in the house and the dangers of smoking for health and the economy. The purpose of this community service activity is to provide education or counseling about the dangers of smoking at home and the dangers of smoking for health and the economy, so that there is an increase in knowledge in the community of Lewomudat Hamlet, Waipaar Village, Talibura District. The method used in community service activities is counseling through three stages, namely the preparation, implementation, and evaluation monitoring stages. This activity was carried out on July 05, 2024 involving 20 people. The results obtained show that there is a significant difference between the level of community knowledge before and after being given educational material or counseling.